EKSTRAK DAUN TEH HIJAU (CAMELLIA SINENSIS) SEBAGAI XANTIOKSIDAN ALAMI MINYAK KELAPA (COCOS NUCIFERA) - Yessyca Octavia; Ruth Chrisnasari; Maria Goretti Marianti P. (Perpustakaan Universitas Surabaya, 2018)
Coconut oil can be used to fulfill the high demand for cooking oil in Indonesia. The quality of coconut oil can decrease because of oxidation. Oxidation can be prevented by adding natural antioxidant such as green tea. The objective of this research was to optimize the process of metabolite extraction with highest antioxidant activity. The solvent used for extraction were ethanol 96%, asetonitril 50% and acetone 25%. Green tea extract was analyzed quantitatively using Total Phenolic Compound (TPC) and 2,2-diphenyl-1-pichrylhydraziyl (DPPH). The crude extract from green tea from maceration using ethanol 96% gave the highest inhibition at about 90,8 ± 0,71%. Thin Layer Chromatography (TLC) analysis showed existence of catechin and myrecetin in the extract. As much as 0,01% was applied as natural antioxidant in coconut oil. The quality of coconut oil observed by iodine value, peroxide value, TBA value, colour and viscosity changed. The result showed that the addition of green tea extract can prevent oxidation rate with efficiency of 1,5.